Sequential layer-by-layer engineered polypyrrole-activated carbon multilayer films: high-energy composite electrode materials for symmetrical supercapacitors. (23rd February 2019) - Sudhakar, Y. N.; Cortiñas, Sara Méndez; Selvakumar, M.
ABSTRACT: Multilayer polypyrrole (PPy))/Activated carbon (AC) composite electrode was potentiostatically prepared on the surface of stainless steel. Numbers of layers were optimized with p-toluene sulphonic acid, benzene sulphonic acid, and camphor sulphonic acid, as concerned with the accessibility of monomers and high capacitance. Surface morphology of successive deposition of PPy/AC layers were observed using SEM and AFM. The performances of each layer have been studied using cyclic voltammetry and AC impedance spectroscopy. The first layer showed specific capacitance of 345 F g −1, whereas in the multilayered film it was 658 F g −1 . Symmetrical supercapacitor were fabricated using multilayer electrodes and compared with single layer electrodes. The properties of supercapacitor showed specific capacitance of 557 F g −1 in a multilayer based supercapacitor, and charge-discharge studies showed excellent stability at the different current density in 0.1M H2 SO4 . Hence, the study provides evidence and scope for using multilayer with optimized materials and electrochemical conditions. Graphical Abstract: